Completion of the swine genome will simplify the production of swine as a large animal biomedical model - Walters Eric M; Wolf Eckhard; Whyte Jeffery J; Mao Jiude; Renner Simone; Nagashima Hiroshi; Kobayashi Eiji; Zhao Jianguo; Wells Kevin D; Critser John K; Riley Lela K; Prather Randall S (BMC, 2012)
Abstract Background Anatomic and physiological similarities to the human make swine an excellent large animal model for human health and disease. Methods Cloning from a modified somatic cell, which can be determined in cells prior to making the animal, is the only method available for the production of targeted modifications in swine. Results Since some strains of swine are similar in size to humans, technologies that have been developed for swine can be readily adapted to humans and vice versa. Here the importance of swine as a biomedical model, current technologies to produce genetically enhanced swine, current biomedical models, and how the completion of the swine genome will promote swine as a biomedical model are discussed. Conclusions The completion of the swine genome will enhance the continued use and development of swine as models of human health, syndromes and conditions.